The Level of Patients’ Satisfaction on Healthcare Service Quality based on SERVQUAL Model in Saudi Private Hospitals: Managerial Perspective - Jehad S. Bani-Hani ,Saleh Abdulhabib Alnahdi (International Journal of Advanced Science and Technology, 2020)
This study was launched for the purpose of investigating the influence of services quality dimensions (SERVQUAL Model) on patients’ satisfaction from hospitals’ managers’ point of view. Data collected from 182 managers of private hospitals located in Jeddah City (KSA). The data analyzed by using different statistical tests and revealed many interesting findings. Some of which describe the demographic characteristics of the unit of analysis. The findings of this study revealed that the most important SERVQUAL dimension is Assurance, while the least important SERVQUAL dimension is Tangibles. As for the level of patients satisfaction the hospitals managers pointed that expected satisfaction more important than perceived satisfaction. The key findings were analytical and inferential, and revealed significant positive correlation relationship between services quality dimensions and patients’ satisfaction, and significant impact for the services quality dimensions on patients level satisfaction. The last section of this study focused on the discussion, conclusions, and implications.